Levels of Teaching of Urdu as Foreign Language - Muhammad Umar Farooq Sial (Zaban-o-Adab, 2023)
As Urdu is emerging as global language, tradition of teaching of Urdu as foreign language is wide spread in different countries and institutions. It is necessary to consider purpose and level of the learners while formulating curricula, teaching methodologies and proportion of basic language skills at different levels of learning. A student may have his own business or educational purpose to learn Urdu language and the curriculum and teaching methodology at basic, intermediate and advanced levels depends upon this purpose. Keeping in view all these factors, there is a need to establish a suitable model at each level.